Building conceptual links between quality attributes in food - Figueiredo, Jeovan de Carvalho; Csillag, João Mario (Review of Business Management, 2010)
The present study has as objective to develop an integrated approach of quality attributes to the researches that study the food consumer behavior. From the review of literature, it was possible to identify three distinct sets of quality attributes. The first of them consists of the functional or hedonic character attributed to the consumption of the food. The second one is composed by the intrinsic and extrinsic attributes. The third group is formed by the attributes that make a product or goods, search or experience, or credence good. The results of this essay show that, separately, these sets of attributes have minor potential to help the enterprise decision, but when used altogether, they can generate precious insights, as consequence of integrated and simultaneous analysis of quality of one same food. Key words: Consumer behavior. Framework. Beef.